Light-cured millineedle platform delivers “nano-pomegranate” for combinatorial electrodynamic therapy and cuproptosis against oral carcinoma - Guoyun Wan; Jiayu Chen; Yingying Zhou; Lina Dou; Dongmei Wang; Nannan Wang; Hongli Chen; Haijiao Wang; Xianwen Wang; Zhijun Yang; Dan Ding (Bioactive Materials)
Monomodal therapies often fail to eradicate tumors due to the complexity of tumorigenesis and microenvironmental resistance. Electrodynamic therapy (EDT) and cuproptosis as emerging antitumor therapies have attracted widespread attention and become the promising strategies for tumor treatment due to their unique advantages. Here, we first time present a light-cured millineedle as a tool for co-delivering a nano-pomegranate (N-PG) platform and Cu2+ by integrating EDT and cuproptosis induction for combined oral cancer treatment. This platform N-PG/NSC consists of Pt-doped dendritic mesoporous large silica nanoparticles (Pt@DLMSN) loaded copper ionophore NSC319726, enabling dual therapeutic actions: (1) N-PG/NSC-based EDT-driven generation of hydroxyl radicals (•OH) via H2O decomposition under electric fields, circumventing hypoxia-related resistance, and (2) NSC imported Cu2+-mediated cuproptosis through mitochondrial dysfunction induced by DLAT oligomerization and Fe-S cluster protein depletion. The millineedle ensures precise and weak-leakage intratumoral delivery, while simultaneously triggering immunogenic cell death (ICD) to prime antitumor immunity. When combined with the TLR7/8 agonist R848, the platform elicits systemic immune activation, effectively suppressing both primary and abscopal oral tumors. As the first reported integration of MN-assisted drug delivery, hypoxia-tolerant EDT, and cuproptosis, this work establishes a translatable paradigm for multimodal cancer therapy, merging localized cytotoxicity with immune reprogramming for enhanced clinical outcomes.